1997
DOI: 10.1007/pl00003393
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of patients with acetabular fractures

Abstract: In the rehabilitation of patients with acetabular fractures, we try to achieve anatomical reconstruction of the joint as well as unlimited mobility. This is important for the patient's reintegration at work and in social life.These aims can only be reached with joint effort of the patient him/herself and all the different specialists concerned with the treatment. Functional physiotherapy should start as early as possible after trauma. Prophylaxis of joint stiffness, thrombosis, pneumonia and soft-tissue ulcers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In general, many authors state that rehabilitation is as important as proper fracture reduction and fixation, although only a few authors describe their rehabilitation protocol extensively. Regarding the post-surgical rehabilitation of fractures of the proximal humerus, acetabulum and tibial plateau, 6 eligible papers (1, 2, 4, I II I II I II I II I II I 8-10) were found, of which 5 discussed the rehabilitation of proximal humerus fractures (1, 2, 8-10) and 1 the rehabilitation of acetabulum fractures (4). No paper addressed protocols for the post-surgical rehabilitation of tibial plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, many authors state that rehabilitation is as important as proper fracture reduction and fixation, although only a few authors describe their rehabilitation protocol extensively. Regarding the post-surgical rehabilitation of fractures of the proximal humerus, acetabulum and tibial plateau, 6 eligible papers (1, 2, 4, I II I II I II I II I II I 8-10) were found, of which 5 discussed the rehabilitation of proximal humerus fractures (1, 2, 8-10) and 1 the rehabilitation of acetabulum fractures (4). No paper addressed protocols for the post-surgical rehabilitation of tibial plateau fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 6 eligible papers, 5 addressed physiotherapeutic/ occupational therapeutic rehabilitation after surgical treatment of proximal humerus fractures (1,2,(8)(9)(10) and one addressed post-surgical physiotherapeutic/ occupational therapeutic rehabilitation of acetabulum fractures (4). No paper describing the rehabilitation of tibial plateau fractures met the selection criteria.…”
Section: Content Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same set of exercises in supine or side-lying abduction is usually postponed until 5-14 days postoperatively. Partial weight-bearing with stepwise progression usually starts 6 weeks postoperatively and full weight bearing is eventually allowed at 10 weeks (Maurer et al, 1997). Recently, interesting information was obtained by direct measurements of acetabular contact pressures during rehabilitation exercises in subject with pressure-instrumented partial endoprostheses where it was found that acetabular pressures may not follow the predicted rank order corresponding to the commonly prescribed temporal order of rehabilitation activities (Givens-Heiss et al, 1992;Tackson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%